To tape or not to tape: annular ligament (pulley) injuries in rock climbers—a systematic review - Robin Larsson; Lena Nordeman; Christina Blomdahl (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background Popularity of rock climbing is steadily increasing. With its inclusion in the Olympic Games this will likely continue. Injuries from rock climbing are also increasing. The most common injury is to the flexor pulley system, consisting of the finger flexors and five annular ligaments (pulleys). Treatment of this injury includes taping of affected fingers, but evaluation of this treatment was previously lacking. The aim of this review was therefore to assess whether taping is associated with better outcomes than non-taping. A secondary aim was to present treatment recommendations or areas for future research. Methods Systematic searches of PubMed, Scopus, SPORTDiscus, Cochrane Library, PEDro and CINAHL. Free text searches of Google Scholar. Citation searching. No restrictions to language, date of publication or study design. Included studies were assessed using Cochrane scale for clinical relevance, by two independent authors. Results were presented in narrative synthesis. Certainty of evidence (GRADE) was assessed by three authors. Review was done according to PICO-protocol and reported according to PRISMA-guidelines. Results After removing duplicates, 595 records were identified. Eight studies and one case report (in nine articles, one poster) were included, consisting of 206 rock climbers, four non-climbers, 23 pairs of cadaver hands. Clinical relevance ranged from 0 to 5 (median 2). Evidence of low to moderate certainty suggests that taping might reduce bowstringing of the finger flexor tendons by 15–22%. Evidence regarding pain, time for return to sports, shearing forces against pulleys, pulley ruptures and maximum voluntary contraction (MVC) were all regarded as “very low”, “very low to low” or “low”, and were not considered reliable. Evidence of moderate certainty suggests that taping has no effect on MVC or muscle activation in uninjured rock climbers. No adverse effects of taping were reported. Conclusion Low to moderate evidence suggests that taping might reduce bowstringing of the finger flexor tendons. Moderate evidence suggests that taping has no effect on MVC or muscle activation in uninjured climbers. For other outcomes more studies evaluating the effects of taping are needed. Trial registration: PROSPERO CRD42021241271, date of registration: 18-04-2021.